The Arden guide to Renaissance drama an introduction with primary sources - Charry, Brinda (London New York Bloomsbury Arden Shakespeare, 2017)
"This companion to early modern drama equips undergraduate students with the information needed to situate the plays in their socio-political, intellectual and literary contexts. Chapters survey important political, cultural and intellectual events and movements, ranging from the Reformation to emerging nationalism to humanism and to print culture. The book also places at students' disposal some of the key primary documents that constitute the discursive context in which the plays are situated. Finally, it introduces them to the major authors and key dramatic texts of the period and emphasises the importance of both a historicist and close-reading approach to better engage with these works. Rather than using various texts to cover this ground, this book provides undergraduate and college-level students embarking on an in-depth exploration of early modern drama with one resource, making both critical and contextual information accessible even as it helps make their approach to the literature more insightful and sophisticated"-- Provided by publisher.
Machine generated contents note: -- Part I -- 1. Politics and Society -- 2. Men and Women -- 3. Travel and Trade -- 4. Humanism -- 5. The stage -- 6. Authors, Books and Readers -- 7. Genre -- 8. Language and Style Part II -- The Alchemist -- Arden of Faversham -- Doctor Faustus -- The Duchess of Malfi -- Hamlet -- Henry V -- The Jew of Malta -- The Knight of the Burning Pestle -- The Roaring Girl -- The Shoemaker's Holiday -- The Spanish Tragedy -- The Tempest -- The Tragedy of Mariam -- Volpone -- Appendices -- Index.
Includes bibliographical references and index.
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- Study and teaching (Higher); English drama -- 17th century -- Study and teaching (Higher).; Renaissance -- England -- Study and teaching (Higher)